Sex and the City : The Complete Season 6 Disc 5 - Star, Darren, 1961-; Nixon, Cynthia; Kim Cattrall; Kristin Davis; Sarah Jessica Parker (USA Hbo Home Video, 1998)
With these eight episodes, HBO's grand sitcom concluded, leaving untold numbers of women--and many men--feeling deprived. The six-year series certainly did not outlast its welcome; the final season is some of the best TV had to offer in 2004. In many ways, the eight episodes served as a single finale, with all four characters approaching a kind of destiny and happiness, the theme of this last half-season (which aired weeks after the first half). Carrie (Sarah Jessica Parker) continues her romance with Russian artist (Mikhail Baryshnikov), a flippantly arrogant man who's been around the block, but able to supply Carrie's needed desire for magic. Miranda (Cynthia Nixon) has settled down with Steve (David Eigenberg), but there is more that will change with her, including her address. Charlotte (Kristin Davis) continues to make baby plans now that the husband slot is filled quite nicely (Evan Handler). Samantha (Kim Cattrall) brings a good sense of drama to the show with a breast-cancer scare. Going down the final stretch--and Samantha's cancer--gives the series a more serious tone, but there's always a jab to tickle the funny bone: Miranda's awkwardness with happiness, Charlotte's latest passion, Carrie typing someplace new, and Samantha getting into Paris Hilton territory. Like any series winding down, there is a wedding, a baby, old faces popping up, and some star-ladened new ones (like creative consultant Julia Sweeney as a nun). In the final two-part episode, "An American in Paris," Carrie faces her romantic destiny, but also solidifies herself as a fashion icon, an Audrey Hepburn for 21st-century television. In the penultimate episode, she asks her friends an emotional question: "What if I never met you?" Certainly fans can ask of themselves the same question and reminisce how much better TV became since they first tuned in these four women of the City.
Four beautiful female New Yorkers gossip about their sex-lives (or lack thereof) and find new ways to deal with being a woman in the 90's.
Language: English Subtitles: English, Dutch, Arabic, Bulgarian, Czech, Hebrew, French, Turkish, Polish, Portuguese, Icelandic, Serbo-Croatian, Romanian, Slovenian
Keywords: Romance; Comedy -- Tv Series